Comparison of the release of microRNAs and extracellular vesicles from platelets in response to different agonists. (4th July 2018) - Ambrose, Ashley R.; Alsahli, Mohammed A.; Kurmani, Sameer A.; Goodall, Alison H.
ABSTRACT: On activation platelets release microRNAs and extracellular vesicles (EV) into circulation. The release of EV from platelets has been shown to be dependent on the agonist; in this study, we investigated whether the microRNA profile or EV released from platelets was also agonist specific. Washed platelets from healthy subjects were maximally stimulated with agonists specific for the receptors for collagen (Glycoprotein VI (GPVI)), thrombin (PAR1/PAR4), or ADP (P2Y1/P2Y12) with/without inhibiting secondary mediators, using aspirin to block cyclooxygenase-1 and apyrase to remove ADP. The released microRNAs were profiled using TaqMan microRNA microarray cards. Platelet-derived EV (pdEV) were characterized by size (Nanoparticle Tracking Analysis, NTA), for procoagulant activity (Annexin-V binding and support of thrombin generation), and for the EV markers CD63 and HSP70. Platelet activation triggered the release of 57–79 different microRNAs, dependent upon agonist, with a core of 46 microRNAs observed with all agonists. There was a high level of correlation between agonists ( r 2 > 0.98; p < 0.0001 for all), and with the microRNA content of the parent platelets ( r 2 > 0.98; p < 0.0001). The 46 microRNAs seen in all samples are predicted to have significant effects on the translation of proteins involved in endocytosis, cell cycle control, and differentiation. MiR-223-3p was the most abundant in all samples and has previously been implicated in myeloid lineage development and demonstrated to have anti-inflammatory effects. Stimulation through GPVI produced a pdEV population with significantly more procoagulant activity than the other agonists. Apyrase significantly reduced microRNA and pdEV release, while aspirin had little effect. These data suggest that all tested agonists trigger the release of a similar microRNA profile while the procoagulant activity of the pdEV was agonist dependent. ADP was shown to play an important role in the release of both microRNAs and pdEV.